Are dopamine-related genotypes risk factors for excessive gestational weight gain? - Goldfield GS; Dowler LM; Walker M; Cameron JD; Ferraro ZM; Doucet E; Adamo KB (Dove Medical Press, 2013)
Gary S Goldfield,1–5 Lauren Marie Dowler,5 Mark Walker,6,7 Jameason D Cameron,3 Zachary M Ferraro,1 Eric Doucet,3 Kristi B Adamo1–31Healthy Active Living and Obesity Research Group, Children's Hospital of Eastern Ontario Research Institute, 2Department of Paediatrics, 3School of Human Kinetics, 4School of Psychology, University of Ottawa, 5Department of Psychology, Carleton University, 6Ottawa Hospital Research Institute, 7Department of Obstetrics and Gynecology, University of Ottawa, Ottawa, ON, CanadaBackground: Excessive gestational weight gain is associated with postpartum weight retention and downstream child obesity. Dopamine plays a critical role in the regulation of energy intake and body weight. The purpose of this study was to examine the relationship between excessive gestational weight gain and dopamine pathway-related polymorphisms, namely the variable nucleotide tandem repeat in the 3´untranslated region (UTR) region of the SLC6A3 (DAT-1) dopamine transporter gene and the 30-base pair variable nucleotide tandem repeat polymorphism of the 5´UTR of the monoamine oxidase-A (MAO-A) gene.Methods: Ninety-three women of mean age 31.7 ± 4.2 years were recruited from the Ottawa and Kingston birth cohort and assessed at 12–20 weeks’ gestation. Mean body mass index was 22.7 ± 2.5 kg/m2. Excessive gestational weight gain was defined according to the 2009 Institute of Medicine guidelines based on body mass index. Genotype analyses were performed using polymerase chain reaction and agarose gel electrophoresis.Results: There was no relationship between the prevalence or magnitude of excessive gestational weight gain among women with the 3´ UTR single nucleotide polymorphism of the DAT-1 gene. However, 70% (19 of 27) of women carrying the MAO-A 4/4 (high activity) allele exceeded recommendations for gestational weight gain compared with 48% (32 of 60) of those with the pooled 3/3, 3/4, and 3/3.5 (low activity) alleles (P < 0.05). Similarly, those with the MAO-A 4/4 allele had significantly greater gestational weight gain than those with the 3/3, 3/4, or 3/3.5 pooled genotypes (19.3 ± 4.1 versus 17.0 ± 5.0 kg, P = 0.03).Conclusion: Carriers of the 4/4 variants of the MAO-A gene may be at increased risk for excessive gestational weight gain.Keywords: gestational weight gain, dopamine genes, monoamine oxidase-A